Availability of a partially acidulated rock phosphate to the sugar cane plant: I. First crop - Malavolta, E.; Pexe, C.A.; Ruivo, F.P.; Carvalho, J.G. de; Guimarães, P.G.; Vitti, G.C. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1982)
The relative efficiency of a partially acidulated and granulated rock phosphate, FAPS, containing 26% total P2O5, 10% citric acid soluble P2O5, 13% ammonium citrate soluble P2O5, 27% total CaO and 7% total S, was compared with that of both simple superphosphate (SS) and ground rock phosphate (FA). The experiment with the sugar cane variety NA 56-79 was set in a red yellow latosol, pH 5.1-5.5, low in P (4 ppm), and with and average available sulphur content (5 ppm as sul fate). The main conclusions were as follows: a) FAPS gave the same yield results provided by SS when used at the same rates based on total P2O5 content; b) sucrose content in the juice was increased by the highest level (16a kg P2O5 of application of FAPS; c) leaf analyses data suggest that FAPS has incre ased yield by supplying both P2O5 and S to the sugar-cane crop.